(untitled) (IUBAT Review, 2025)
Metamaterial absorbers (MMAs) have appeared as innovative structures capable of effectively manipulating electromagnetic (EM) waves beyond the capabilities of natural materials. This review provides a comprehensive summary of narrowband and wideband MMAs, discussing their design strategies, working principles, and application-specific configurations. This study intends to point out current growths that enable high absorption performance, polarization insensitivity, angular stability, and frequency selectivity. A variety of unit cell structures, resonator shapes, and material selections are explored to realize their roles in achieving desired absorption features. The review categorizes MMAs based on their absorption bandwidth, structural parameters and performance metrics such as quality factor, sensitivity and frequency tunability. Methods like impedance matching, resonant mode coupling and equivalent circuit modeling are investigated to enlighten the physical mechanism of absorption. Crucial applications in wireless communication, radar cross-section reduction, energy harvesting, biomedical and environmental sensing are also discussed. Meanwhile, comparisons among current designs are presented in tabular form to back future designers in choosing ultimate MMA configurations. The paper concludes by summarizing the design challenges and providing visions into emerging trends and potential future guidelines in MMA technology. IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 145-175